Research on Dynamics and Large Angle Attitude Robust Control Technology of "Dumbbell" Spacecraft. Issue 1 (1st April 2022) - Ai, Qingmu; Fan, Hongwei; Wang, Qian; Liu, Dun; Li, Shunli
Abstract: In this work, the deployment state dynamics modeling and large angle attitude control of "dumbbell" spacecraft are studied. Firstly, based on the principle of multi-body dynamics, the rigid flexible coupling dynamic model is established by using Newton Euler method and finite element technology. Secondly, using Lagrange equations of the second type, the vibration equation is established. Furthermore, the unconstrained modal method is used to solve the unconstrained modal frequencies and formations. Finally, according to the large angle control requirements of "dumbbell" spacecraft, its stability is analyzed. A PD controller with robust term is designed to realize the large angle attitude control.